2017
DOI: 10.1590/0102-311x00074416
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento e uso de cigarros eletrônicos e percepção de risco no Brasil: resultados de um país com requisitos regulatórios rígidos

Abstract: Resumo: Devido às incertezas sobre o impacto dos cigarros eletrônicos na saúde, o Brasil adotou, em 2009, regulamentação que proibiu venda, importação e propaganda desses produtos até que fabricantes possam demonstrar que são seguros e/ou efetivos na cessação de fumar. O objetivo do estudo foi analisar entre fumantes brasileiros: (1) conhecimento sobre existência de cigarros eletrônicos, uso na vida, e uso recente; (2) percepção de risco sobre cigarros eletrônicos comparados a cigarros convencionais; e (3) fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
20

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 11 publications
0
8
0
20
Order By: Relevance
“…The prevalence of e-cigarette use was associated with being younger, having parents with a higher level of education, and having smokers in the family 15 . Although the prevalence of regular e-cigarette use was lower than that reported for other countries, 16 , 17 as well as being lower that reported in a study evaluating a sample of individuals over 18 years of age in the Brazilian cities of Rio de Janeiro, São Paulo, and Porto Alegre, 18 the Oliveira et al study 15 calls attention to the high rate of awareness of e-cigarettes.…”
mentioning
confidence: 61%
“…The prevalence of e-cigarette use was associated with being younger, having parents with a higher level of education, and having smokers in the family 15 . Although the prevalence of regular e-cigarette use was lower than that reported for other countries, 16 , 17 as well as being lower that reported in a study evaluating a sample of individuals over 18 years of age in the Brazilian cities of Rio de Janeiro, São Paulo, and Porto Alegre, 18 the Oliveira et al study 15 calls attention to the high rate of awareness of e-cigarettes.…”
mentioning
confidence: 61%
“…Data about the use of electronic cigarettes in in Brazil is very limited and indicates that 4.6% of adult smokers have tried cigarettes or used electronic cigarettes in the last 6 months (the study did not distinguish between experimentation and continuous use) 72 . Another study carried out in university students revealed that 2.7% had tried it, and 0.6% had regular use of it 73 .…”
Section: Use and Marketing Of Esdsmentioning
confidence: 89%
“…Studies on the use of ESDs in Brazil [72][73][74] have shown that the prevalence of use of these products was the lowest among countries participating in the International Tobacco Control Survey (ITC), but their use in life was not so different when compared to these other countries. Another important finding of the study is that a significant fraction of smokers, independent of country or level of regulatory restriction, believed that ESDs were safer than conventional cigarettes 72,74 .…”
Section: Use and Marketing Of Esdsmentioning
confidence: 99%
“…Na ausência de um instrumento validado na língua portuguesa, foi elaborado um questionário (quadro 1) com base em trabalhos previamente publicados 16,20 . Os dados coletados foram organizados em planilhas e os participantes divididos em três grupos: G1ingressantes (1 a e 2 a fases do curso); G2intermediários (4 a e 5 a fases); e G3 -concluintes (9 a e 10 a fases).…”
Section: Metodologiaunclassified
“…O número de usuários de CE vem aumentando a cada ano, e levantamentos mostram a existência de pelo menos 500 marcas diferentes no mercado, com considerável variabilidade no design do produto 13,14 . No Brasil, a comercialização, importação e propaganda de CE está proibida, assim como de quaisquer acessórios e refis a eles destinados 15,16 ; porém, há evidências de sua comercialização de forma ilegal 16 .…”
Section: Introductionunclassified